The health of nations: Society and law beyond the state - Allott, Philip (Cambridge University, 2013)
Globalisation challenges our traditional social structures, with international systems such as the European Union, taking power over the power of states and governments. We must rethink the ideas which have made our national systems work. Allott seeks to develop these ideas in new ways to meet the new global challenges.